2022
DOI: 10.3389/fphar.2022.973246
|View full text |Cite
|
Sign up to set email alerts
|

Immune-related adverse events of biological immunotherapies used in COVID-19

Abstract: The use of biological immunotherapeutic drugs is one of the options currently being evaluated and employed to manage COVID-19, specifically monoclonal antibodies, which have shown benefit by regulating the excessive immune response seen in patients with severe infection, known as a cytokine storm. Tocilizumab has received particular importance for this clinical application, as has sarilumab. Both drugs share a substantial similarity in terms of pharmacodynamics, being inhibitors of the interleukin six receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…Thus, some of biological immunotherapies, mainly monoclonal antibodies, have been evaluated aiming at regulating the excessive immune response seen in SARS-CoV-2 patients with severe infection. The two classes of IL-6 inhibitors, the monoclonal antibodies against the IL-6 receptor, including sarilumab, tocilizumab, clazakizumab, olokizumab and the anti-IL-6 monoclonal antibody siltuximab, were investigated in various clinical trials and no clear beneficial were found ( Baracaldo-Santamaría et al, 2022 ). In addition, it was reported that the treatment with these antibodies caused acute pneumonitis, idiopathic pulmonary fibrosis, and exacerbation of rheumatoid arthritis-associated interstitial lung disease in a fraction of patients.…”
Section: Sars-cov-2-associated Pneumoniamentioning
confidence: 99%
“…Thus, some of biological immunotherapies, mainly monoclonal antibodies, have been evaluated aiming at regulating the excessive immune response seen in SARS-CoV-2 patients with severe infection. The two classes of IL-6 inhibitors, the monoclonal antibodies against the IL-6 receptor, including sarilumab, tocilizumab, clazakizumab, olokizumab and the anti-IL-6 monoclonal antibody siltuximab, were investigated in various clinical trials and no clear beneficial were found ( Baracaldo-Santamaría et al, 2022 ). In addition, it was reported that the treatment with these antibodies caused acute pneumonitis, idiopathic pulmonary fibrosis, and exacerbation of rheumatoid arthritis-associated interstitial lung disease in a fraction of patients.…”
Section: Sars-cov-2-associated Pneumoniamentioning
confidence: 99%
“…Tocilizumab is a recombinant human monoclonal antibody, while sarilumab is a recombinant human IgG1 antibody. Both therapies function through the same mechanism of action, which involves targeting the IL-6 receptor protein responsible for immune systeminduced inflammation and inhibiting the IL-6 signaling pathway [117].…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Furthermore, a study conducted by Soin et al comparing the tocilizumab group to the standard care group in terms of COVID-19 development on day 14 revealed additional adverse reactions associated with tocilizumab. These adverse reactions encompassed anaphylactic reactions, anaphylactic shock, renal failure, pulmonary fibrosis, drug-induced liver injury, pancreatitis, pancytopenia, serious infections, and hypersensitivity reactions [117,128].…”
Section: Adverse Drug Reactionmentioning
confidence: 99%
“…Other adverse effects include interstitial lung disease [342] , hepatic disorders [343] , and immunogenicity to the drug [344] . Common adverse events of siltuximab are pruritus, hypertension, nausea, vomiting, fatigue, and neutropenia [345] , [346] . Hyperlipidemia, cellulitis, and more severe events like urinary retention, polycythemia, leukopenia, lymphopenia, and hypersensitivity reactions were reported with the administration of siltuximab [345] , [346] , [347] .…”
Section: Introductionmentioning
confidence: 99%
“…Common adverse events of siltuximab are pruritus, hypertension, nausea, vomiting, fatigue, and neutropenia [345] , [346] . Hyperlipidemia, cellulitis, and more severe events like urinary retention, polycythemia, leukopenia, lymphopenia, and hypersensitivity reactions were reported with the administration of siltuximab [345] , [346] , [347] . Increased risk of infections and cancer, hematologic effects, headache, joint pains, anaphylaxis, skin conditions, abdominal pains, and diarrhea are mentioned as adverse effects of anakinra [348] , [349] .…”
Section: Introductionmentioning
confidence: 99%